WORKING CAPITAL: GROWTH POTENTIAL AND OPERATING CASH CYCLE (COC) CASE OF A COMPANY MANUFACTURING - Porlles Loarte, José Angel (2008)
The Country is found in a situation of growth. To the margin of the financial crisis, diverse industrial sectors come growing to expectant rates. Therefore, a lot of of these businesses they require financing to maintain their growth. The proposed present is a contribution of a model improved for the decision of the cash or capital circulating necessary to maintain its operating cycle of the business, besides know its capacity of effective autogenerated for cover future growths of the sales.